Climate-Related Limitations on Photosynthesis and Drought-Resistance Strategies of Ziziphus spina-christi - Zait, Yotam; Schwartz, Amnon (Frontiers in Forests and Global Change, 2018)
Current climatic changes are subjecting plants to increasing amounts of abiotic stress and intensifying desertification in many regions. The identification of tree species that can survive extremely limited water conditions may assist in limiting regional desertification processes and mitigating the greenhouse effect. Ziziphus spina-christi is a thermophilic tree from Sudan that is highly tolerant of heat and drought. In recent years, this tree has become more abundant in the Mediterranean region. In order to predict how a warm and dry climate influences the successful establishment of this species, we compared the seasonal photosynthesis of Z. spina-christi trees growing in a Mediterranean climate and a semi-arid climate. At each site, we measured the seasonal changes in gas exchange, chlorophyll fluorescence and stem water potential (Ψstem). We quantitatively compared the seasonality of factors that limit photosynthesis: stomatal conductance (gs), mesophyll conductance (gm) and maximal capacity for Rubisco carboxylation (Vcmax). Our results revealed differences in the seasonality of the trees’ photosynthetic capacities, as well as different drought avoidance and tolerance strategies at the two different sites. Trees grown at the Mediterranean-climate site exhibited high photosynthetic activity during winter-spring and summer, but significantly less photosynthetic activity during the fall drought. During periods of drought, the overall limitation of photosynthesis was mostly due to strong stomatal regulation. Trees in the Mediterranean sites compensate for their lower gs with a larger gm and high Vcmax. In contrast, at the semi-arid site, peak photosynthesis was observed in the spring and fall. The reduced photosynthesis during the summer drought and the period of low temperatures during the winter were associated with greater reduction in gm, as compared to gs, and increased investment in photoprotective mechanisms (NPQ and photorespiration). Relatively low midday Ψstem was observed at both sites during the driest period (>-2.2 MPa), revealing that this species employs drought-avoidance strategies. Our results demonstrate how Z. spina-christi could be an attractive tree for afforestation programs in semi-arid areas and how climate change may give it an ecological advantage that may lead to its becoming more widely distributed across this region in future decades.